Regional inequality of higher education in China and the role of unequal economic development - Frank Bickenbach; Wan-Hsin Liu (Kiel Institute for the World Economy (IfW), 2011)
Over the past decade the scale of higher education in China has expanded substantially. Regional development policies attempted to make use of the scale expansion as a tool to reduce the inequality of higher education among different regions with different development levels through providing the poor regions preferential treatment and support in this regard. This paper analyses a provincial dataset (1997-2008), aiming to provide comprehensive quantitative evidence for the development of inequality of higher education opportunities across provinces in China over the period of the scale expansion, taking different sizes and economic development levels of provinces into account. Results show that the regional inequality of higher education relative to provinces' different population sizes clearly decreased over the research period. Accompanying the reduction in overall inequality across provinces, the inequality between the poor and the rich regions actually increased over the same period. However, the increase was realised in favour of the poor region. The empirical results are consistent with the policy orientation of reforming the higher education system and of promoting regional development in China over the past decade.
Keywords: C43; I23; I28; R53; R58; 330; Higher education; regional inequality; China; Theil index; Studium; Regionale Disparität; Regionale Entwicklung; China